2022
DOI: 10.1080/21655979.2022.2051841
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long noncoding RNA HUMT inhibits the proliferation and metastasis by regulating miR-455-5p/LRP4 axis in hepatocellular carcinoma

Abstract: The present study aimed at investigating the effects and mechanism of long noncoding RNA highly upregulated in metastatic triple-negative breast cancer lymph node (lncRNA HUMT) in hepatocellular carcinoma (HCC). Quantitative real-time polymerase chain reaction was used to assess the expression of HUMT, microRNA (miR)-455-5p, and low-density lipoprotein receptor-related protein 4 (LRP4) in HCC tissues. Colony forming and 5-ethynyl-2′-deoxyuridine assays were performed to assess cell proliferation. Transwell ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Many proteins are associated with BC survival in our study. Previous studies have indicated that high expression of LRP4 can inhibit the proliferation, invasion, and migration of hepatocellular carcinoma cells by affecting the miR-455-5p/LRP4 axis (Zou et al 2022). LRP4 is positively associated with BC survival, which suggests the protective role of LRP4.…”
Section: Discussionmentioning
confidence: 91%
“…Many proteins are associated with BC survival in our study. Previous studies have indicated that high expression of LRP4 can inhibit the proliferation, invasion, and migration of hepatocellular carcinoma cells by affecting the miR-455-5p/LRP4 axis (Zou et al 2022). LRP4 is positively associated with BC survival, which suggests the protective role of LRP4.…”
Section: Discussionmentioning
confidence: 91%